Preparation method of aerogel composite material uniformly doped with opacifying agent
By using a combination process of light-shielding modification liquid and silica sol in aerogel composite, uniform doping of light-shielding agent and low thermal conductivity preparation of aerogel composite material is achieved, and the separation under high temperature environment in the prior art is solved The problem of thermal performance degradation provides excellent thermal insulation performance.
Patent Information
- Application Number
- CN202411478203.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-18
AI Technical Summary
The existing aerogel composite materials have deteriorated thermal insulation performance due to thermal radiation in high temperature environments, and the light shielding agent cannot be uniformly doped in the fiber felt, resulting in a low thermal conductivity.
By mixing the precursor liquid with ethanol, the light shielding modification liquid is prepared, soaking the substrate and heat treatment are carried out, combining the gel and aging process of silica sol, and using CO2 supercritical drying technology to achieve uniform doping of the light shielding agent and aerogel composite material. preparation.
The uniform doping of sunscreen agents in aerogel composite materials is achieved, which reduces thermal conductivity and improves thermal insulation performance, and provides excellent thermal insulation effect especially in high temperature environments.
Smart Images

Figure CN119462064A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aerogel composite materials, and in particular relates to a method for preparing an aerogel composite material uniformly doped with a sunscreen. Background Art
[0002] Aerogel has the characteristics of low density, high specific surface area, high porosity and pore volume due to its three-dimensional nanoporous structure, making it a solid material with the lowest thermal conductivity and the best thermal insulation performance. Since aerogel is relatively brittle as a whole, its skeleton is prone to break under the action of external forces, so it is often compounded with fiber felt to obtain composite products.
[0003] Since aerogel has a rich three-dimensional network skeleton and a nano-scale porous structure, the heat loss in heat conduction and heat convection is increased, thus having good thermal insulation performance. However, as the temperature rises, thermal radiation becomes the main mode of heat transfer. Doping with sunscreens can effectively reduce the thermal conductivity under high-temperature thermal radiation and thus improve its thermal insulation performance. Commonly used sunscreens include carbon black, titanium oxide, zirconium oxide, and silicon carbide, etc. These sunscreens are usually added to the prepared silica sol in the form of powder during the sol-gel stage and impregnated into the fiber felt together with the glue. However, the fiber felt has small pores and will become a natural filter, causing the sunscreen powder to gather on the surface of the fiber felt and cannot be evenly dispersed in the fiber felt. Summary of the invention
[0004] Purpose of the invention: To provide a method for preparing an aerogel composite material uniformly doped with a sunscreen agent, thereby solving the above-mentioned problems existing in the prior art.
[0005] Technical solution: A method for preparing an aerogel composite material uniformly doped with a sunscreen, comprising the following steps: Prepare light-shielding modification solution: The precursor solution and ethanol are mixed in a ratio of 1: (0.5-20), and stirred at a rate of 60-500 rpm for 20 min using a mechanical stirrer in a temperature range of 0-40°C to obtain a light-shielding modified solution; Prepare the substrate: The substrate is placed in the light-shielding modification liquid, and the substrate is completely immersed in the light-shielding modification liquid. The substrate is soaked at a temperature of 0-40° C. for 2 minutes, and then taken out and sent to a steamer for soaking, and then taken out and dried to obtain a dry substrate, and then the dry substrate is heat-treated to obtain a light-shielding substrate; Preparation of silica sol: Ethyl silicate, ethanol, deionized water, ammonium fluoride and ammonia water are prepared in a mass ratio of 1: (1.5-15): (0-0.3): (0.01-0.05): (0.01-0.05) to obtain silica sol; Preparation of aerogel composites: The light-shielding substrate is completely immersed in the silica sol, and an aerogel composite material is obtained through gelation, aging, hydrophobic modification and supercritical drying.
[0006] Preferably, the precursor solution is one of tetrabutyl titanate, isopropyl titanate, tetrabutyl zirconate, and tetraisopropyl zirconate.
[0007] Preferably, the process of substrate wetting and drying is as follows: After the steamer is preheated to a temperature of 85°C and a humidity of 85%, the substrate soaked in the light-shielding modification liquid is placed in the steamer in the form of a sheet; soaked with water vapor for 2-12 hours; Place the substrate soaked in the light-shielding modification liquid into a steam oven at a temperature of 85°C and a humidity of 85%; The soaked substrate is taken out and dried for 0.5-20 hours to obtain a dry substrate, wherein the drying method is one of natural air drying, hot air drying, vacuum drying and microwave drying.
[0008] Preferably, the natural air drying is performed by placing the mixture at room temperature for 5-20 hours; The hot air drying is carried out in an oven, and after the oven is preheated to 80° C., the sheet substrate is placed on a tray in the oven and dried for 5-10 hours; The vacuum drying is carried out in an oven, and after the oven is preheated to 60°C and the vacuum degree is -0.08MPa, the sheet substrate is placed on a tray in the oven and dried for 5-10 hours; The microwave drying adopts a microwave drying oven with a microwave power of 1000W. After the microwave drying oven is preheated to 70°C, the substrate is placed in the microwave drying oven and dried for 1-2 hours.
[0009] Preferably, the drying substrate is heat treated as follows: The heat treatment temperature is 300-1500°C, and the temperature is increased to a predetermined temperature at a heating rate of 5°C / min, and then the temperature is kept for 2 hours and then taken out and naturally cooled to room temperature.
[0010] Preferably, the specific process of preparing silica sol is as follows: At a temperature of 0-40° C., ethanol, ethyl silicate and deionized water are added to a container in sequence, and then stirred at a rate of 60-500 rpm using a mechanical stirrer for 5-15 min. Ammonium fluoride and ammonia water are then added and stirred for 5-10 min.
[0011] Preferably, the hydrophobic modifier is a mixed solution of dimethyldiethoxysilane, ammonium fluoride and ethanol, wherein the volume ratio of dimethyldiethoxysilane, ammonium fluoride and ethanol is 1: (0.05-0.15): (10-25).
[0012] Preferably, the process for preparing the aerogel composite material is as follows: After the shading substrate is completely immersed in the silica sol, it undergoes a gelation and aging process of 2 to 48 hours. During this process, when the silica sol is converted into a wet gel, the wet gel is combined with a hydrophobic modifier for hydrophobic modification treatment, and the modification treatment lasts for 12 to 40 hours.
[0013] Preferably, after the hydrophobic modification of the wet gel is completed, supercritical drying is performed using CO2 supercritical drying, with a supercritical drying pressure of 6-8 MPa, a drying temperature of 30-50 degrees, and a drying time of 6-8 hours.
[0014] Beneficial effect: The present invention relates to a method for preparing an aerogel composite material uniformly doped with a sunscreen agent, wherein a liquid sunscreen modification liquid is obtained by mixing a driving liquid with ethanol in a predetermined proportion to soak a substrate, which can not only realize uniform doping of the substrate with the sunscreen modification agent and avoid the phenomenon of sunscreen agent agglomeration and enrichment, but also can adjust the content of the sunscreen agent inside the fiber felt by changing the formula of the sunscreen modification liquid, and control the crystal type of the sunscreen agent by controlling the heat treatment temperature. Through basic raw materials and simple processes, an aerogel composite material uniformly doped with a sunscreen agent having low thermal conductivity and good thermal insulation performance can be prepared, which can provide excellent thermal insulation performance in a high temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a flowchart of the production process of the present invention. DETAILED DESCRIPTION
[0016] Example 1 like Figure 1 As shown, the present invention provides a technical solution: a method for preparing an aerogel composite material uniformly doped with a sunscreen, comprising the following steps: Prepare light-shielding modification solution: The precursor solution is mixed with ethanol in a ratio of 1: (0.5-20), and stirred at a temperature range of 0-40° C. at a rate of 60-500 rpm for 20 min using a mechanical stirrer to obtain a light-shielding modified solution, wherein the precursor solution is one of tetrabutyl titanate, isopropyl titanate, tetrabutyl zirconate, and tetraisopropyl zirconate; Prepare the substrate: The substrate is placed in the light-shielding modification liquid. At this time, the substrate is completely immersed in the light-shielding modification liquid. The substrate is soaked at a temperature of 0-40°C for 2 minutes, then taken out and sent to a steamer for soaking, then taken out and dried. The soaking and drying process of the substrate is as follows: After the steamer is preheated to a temperature of 85°C and a humidity of 85%, the substrate soaked in the light-shielding modification liquid is placed in the steamer in the form of a sheet; soaked with water vapor for 2-12 hours; Place the substrate soaked in the light-shielding modification liquid into a steam oven at a temperature of 85°C and a humidity of 85%; The soaked substrate is taken out and dried for 0.5-20 hours to obtain a dry substrate, wherein the drying method is one of natural air drying, hot air drying, vacuum drying, and microwave drying, and the natural air drying is placed at room temperature and left to stand for 5-20 hours; The hot air drying is carried out in an oven, and after the oven is preheated to 80° C., the sheet substrate is placed on a tray in the oven and dried for 5-10 hours; The vacuum drying is carried out in an oven, and after the oven is preheated to 60°C and the vacuum degree is -0.08MPa, the sheet substrate is placed on a tray in the oven and dried for 5-10 hours; The microwave drying uses a microwave drying oven with a microwave power of 1000W. After the microwave drying oven is preheated to 70°C, the substrate is placed in the microwave drying oven for drying for 1-2 hours. When the soaked substrate is completely dried, a dry substrate is obtained. The dry substrate is then heat-treated to obtain a light-shielding substrate. The heat treatment process of the dry substrate is as follows: The heat treatment temperature is 300-1500°C. After heating to a predetermined temperature at a heating rate of 5°C / min, the temperature is kept for 2 hours and then taken out and naturally cooled to room temperature to obtain a heat-treated light-shielding substrate.
[0017] Preparation of silica sol: Ethyl silicate, ethanol, deionized water, ammonium fluoride and ammonia water are prepared according to a mass ratio of 1: (1.5-15): (0-0.3): (0.01-0.05): (0.01-0.05) to obtain silica sol. The specific process of preparing silica sol is as follows: At a temperature of 0-40° C., ethanol, ethyl silicate and deionized water are added to a container in sequence, and then stirred at a rate of 60-500 rpm using a mechanical stirrer for 5-15 min. Ammonium fluoride and ammonia water are then added and stirred for 5-10 min.
[0018] Preparation of aerogel composites: The light-shielding substrate is completely immersed in the silica sol, and an aerogel composite material is obtained through gelation, aging, hydrophobic modification and supercritical drying, wherein the hydrophobic modifier is a mixed solution of dimethyldiethoxysilane, ammonium fluoride and ethanol, wherein the volume ratio of dimethyldiethoxysilane, ammonium fluoride and ethanol is 1: (0.05-0.15): (10-25); After the shading substrate is completely immersed in the silica sol, it undergoes a gelation and aging process of 2 to 48 hours. During this process, when the silica sol is converted into a wet gel, the wet gel is combined with a hydrophobic modifier for hydrophobic modification. The modification treatment lasts for 12 to 40 hours. After the hydrophobic modification treatment of the wet gel is completed, supercritical drying is performed using CO2 supercritical drying. The supercritical drying pressure is 6~8MPa, the drying temperature is 30~50 degrees, and the drying time is 6~8h.
[0019] When tetrabutyl titanate is used as the precursor solution and polyacrylonitrile fiber felt is used as the substrate to prepare aerogel composite materials: Tetrabutyl titanate and ethanol were mixed in a mass ratio of 1:5 and stirred for 20 minutes to obtain a sunscreen modified liquid.
[0020] After the polyacrylonitrile fiber felt is completely immersed in the modification liquid for 2 minutes, it is taken out and sent to a steamer at a temperature of 85°C and a humidity of 85% to be soaked in water vapor for 4 hours. The modified polyacrylonitrile fiber felt is taken out from the steamer and dried by natural air drying for 6 hours. After that, the modified polyacrylonitrile fiber felt is heat treated at 300°C for 2 hours.
[0021] Preparation of silica sol: The mass ratio of ethyl silicate, ethanol, deionized water, ammonium fluoride and ammonia water is 1:5:0.1:0.03:0.03 to prepare silica sol.
[0022] The heat-treated substrate was immersed in silica sol, then gelled and aged for 24 hours, and a mixed solution of dimethyldiethoxysilane, ammonium fluoride and ethanol was used as a hydrophobic modifier for hydrophobic modification for 24 hours. Finally, an aerogel composite material uniformly doped with a sunscreen agent was obtained by CO2 supercritical drying. The thermal conductivity of the aerogel composite material uniformly doped with a sunscreen agent at 500°C was 0.0420W / (m∙K), which met the RoHS directive and REACH regulations, and the flame retardant grade was UL94-V0.
[0023] Example 2 When tetrabutyl zirconate is used as the precursor solution and aluminum silicate fiber felt is used as the substrate to prepare aerogel composite materials: Tetrabutyl zirconate and ethanol were mixed at a mass ratio of 1:10 and stirred for 20 minutes to obtain a sunscreen modified liquid.
[0024] After the aluminum silicate fiber felt was soaked in the modification liquid for 2 minutes, it was taken out and sent to a steamer at a temperature of 85°C and a humidity of 85% to be soaked in water vapor for 7 hours. The modified aluminum silicate fiber felt was taken out from the steamer and dried by hot air drying for 4 hours. Subsequently, it was heat treated at 1200°C for 1.5 hours.
[0025] Preparation of silica sol The mass ratio of ethyl silicate, ethanol, deionized water, ammonium fluoride and ammonia water is 1:10:0.2:0.04:0.04 to prepare silica sol.
[0026] The aluminum silicate fiber felt modified with the sunscreen agent was immersed in silica sol, and the gel aging time was 36 hours. A mixed solution of dimethyldiethoxysilane, ammonium fluoride and ethanol was used as a hydrophobic modifier for hydrophobic modification, wherein the mass ratio of dimethyldiethoxysilane, ammonium fluoride and ethanol was 1:0.1:20, and the modification time was 30 hours. Finally, the sunscreen agent-uniformly doped aerogel composite material was obtained by CO2 supercritical drying. The prepared sunscreen agent-uniformly doped aerogel composite material had a thermal conductivity of 0.0370W / (m∙K) at 500℃, met the RoHS directive and REACH regulations, and had a flame retardant grade of UL94-V0.
[0027] Example 3 When isopropyl titanate is used as the precursor solution and mullite fiber felt is used as the substrate to prepare aerogel composite materials uniformly doped with sunscreen: Isopropyl titanate and ethanol were mixed in a mass ratio of 1:15 and stirred for 20 minutes to obtain a sunscreen modified liquid.
[0028] After soaking the mullite fiber felt in the modified liquid for 2 minutes, it was taken out and sent to a steamer with a temperature of 85°C and a humidity of 85% for 6 hours. The modified mullite fiber felt was dried by microwave drying for 1 hour. Subsequently, it was heat treated at 1500°C for 1.5 hours.
[0029] Preparation of silica sol The mass ratio of ethyl silicate, ethanol, deionized water, ammonium fluoride and ammonia water is 1:8:0.15:0.03:0.03 to prepare silica sol.
[0030] The mullite fiber felt modified with sunscreen agent was immersed in silica sol, the gel aging time was 24 hours, and a mixed solution of dimethyldiethoxysilane, ammonium fluoride and ethanol was used as a hydrophobic modifier for hydrophobic modification, wherein the mass ratio of dimethyldiethoxysilane, ammonium fluoride and ethanol was 1:0.1:15, and the modification time was 24 hours. Finally, the sunscreen agent-uniformly doped aerogel composite material was obtained by CO2 supercritical drying. The prepared sunscreen agent-uniformly doped aerogel composite material had a thermal conductivity of 0.0350W / (m∙K) at 500℃, met the RoHS directive and REACH regulations, and had a flame retardant grade of UL94-V0.
[0031] The preferred embodiments of the present invention are described in detail above; however, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, various equivalent transformations can be made to the technical solutions of the present invention, and these equivalent transformations all belong to the protection scope of the present invention.
Claims
1. A method for preparing an aerogel composite material uniformly doped with a sunscreen, characterized in that: The following steps are involved: Prepare light-shielding modification solution: The precursor solution and ethanol are mixed in a ratio of 1: (0.5-20), and stirred at a rate of 60-500 rpm for 20 min using a mechanical stirrer in a temperature range of 0-40°C to obtain a light-shielding modified solution; Prepare the substrate: The substrate is placed in the light-shielding modification liquid, and the substrate is completely immersed in the light-shielding modification liquid. The substrate is soaked at a temperature of 0-40° C. for 2 minutes, and then taken out and sent to a steamer for soaking, and then taken out and dried to obtain a dry substrate, and then the dry substrate is heat-treated to obtain a light-shielding substrate; Preparation of silica sol: Ethyl silicate, ethanol, deionized water, ammonium fluoride and ammonia water are prepared in a mass ratio of 1: (1.5-15): (0-0.3): (0.01-0.05): (0.01-0.05) to obtain silica sol; Preparation of aerogel composites: The light-shielding substrate is completely immersed in the silica sol, and an aerogel composite material is obtained through gelation, aging, hydrophobic modification and supercritical drying.
2. The method for preparing an aerogel composite material uniformly doped with a sunscreen according to claim 1, characterized in that: The precursor solution is one of tetrabutyl titanate, isopropyl titanate, tetrabutyl zirconate and tetraisopropyl zirconate.
3. The method for preparing an aerogel composite material uniformly doped with a sunscreen according to claim 1, characterized in that: The process of substrate wetting and drying is as follows: After the steamer is preheated to a temperature of 85°C and a humidity of 85%, the substrate soaked in the light-shielding modification liquid is placed in the steamer in the form of a sheet; soaked with water vapor for 2-12 hours; Place the substrate soaked in the light-shielding modification liquid into a steam oven at a temperature of 85°C and a humidity of 85%; The soaked substrate is taken out and dried for 0.5-20 hours to obtain a dry substrate, wherein the drying method is one of natural air drying, hot air drying, vacuum drying and microwave drying.
4. The method for preparing an aerogel composite material uniformly doped with a sunscreen according to claim 3, characterized in that: The natural air drying is carried out by placing the mixture under room temperature for 5-20 hours; The hot air drying is carried out in an oven, and after the oven is preheated to 80° C., the sheet substrate is placed on a tray in the oven and dried for 5-10 hours; The vacuum drying is carried out in an oven, and after the oven is preheated to 60°C and the vacuum degree is -0.08MPa, the sheet substrate is placed on a tray in the oven and dried for 5-10 hours; The microwave drying adopts a microwave drying oven with a microwave power of 1000W. After the microwave drying oven is preheated to 70°C, the substrate is placed in the microwave drying oven and dried for 1-2 hours.
5. The method for preparing an aerogel composite material uniformly doped with a sunscreen according to claim 1, characterized in that: The process of heat treatment of dry substrate is as follows: The heat treatment temperature is 300-1500°C, and the temperature is increased to a predetermined temperature at a heating rate of 5°C / min, and then the temperature is kept for 2 hours and then taken out and naturally cooled to room temperature.
6. The method for preparing an aerogel composite material uniformly doped with a sunscreen according to claim 1, characterized in that: The specific process of preparing silica sol is as follows: At a temperature of 0-40° C., ethanol, ethyl silicate and deionized water are added to a container in sequence, and then stirred at a rate of 60-500 rpm using a mechanical stirrer for 5-15 min. Ammonium fluoride and ammonia water are then added and stirred for 5-10 min.
7. The method for preparing an aerogel composite material uniformly doped with a sunscreen according to claim 1, characterized in that: The hydrophobic modifier is a mixed solution of dimethyldiethoxysilane, ammonium fluoride and ethanol, wherein the volume ratio of dimethyldiethoxysilane, ammonium fluoride and ethanol is 1: (0.05-0.15): (10-25).
8. The method for preparing an aerogel composite material uniformly doped with a sunscreen according to claim 7, characterized in that: The process of preparing aerogel composite materials is as follows: After the shading substrate is completely immersed in the silica sol, it undergoes a gelation and aging process of 2 to 48 hours. During this process, when the silica sol is converted into a wet gel, the wet gel is combined with a hydrophobic modifier for hydrophobic modification treatment, and the modification treatment lasts for 12 to 40 hours.
9. The method for preparing an aerogel composite material uniformly doped with a sunscreen according to claim 8, characterized in that: After the hydrophobic modification of the wet gel is completed, supercritical drying is carried out using CO2 supercritical drying, with a supercritical drying pressure of 6~8MPa, a drying temperature of 30~50 degrees, and a drying time of 6~8h.
Citation Information
Cited By
Preparation method of in-situ modified doped infrared opacifying agent aerogel composite material
CN121342403A